Difficulties in Pronunciation in Teaching English (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The purpose of this article is to analyze the most common pronunciation difficulties faced by ESL learners and explore effective teaching strategies to address these challenges. Factors leading to these problems are interference of the native language, learners' age, attitude, and their insufficient knowledge of phonology and phonetics systems of the English language. Besides, phonetic ability was reported as the factor that mostly caused problems in phonetics learning. It could be concluded that the opinion of the difference in sound systems between English and the native language and some factors, including phonetic ability, native language, prior English pronunciation learning, instruction, and motivation, caused the students' problem in phonetics learning as well. Teaching students how to use their mouth, tongue, throat, and voice (articulatory phonetics) helps them produce the sounds of English. Understanding where the sounds are produced (place of articulation) and how (manner of articulation) helps them visualize movements that would not normally be visible.